Disclosure of Ijtihad: The Changes of the Early Time of Dawn as a Sharia and Science Integration Effort - Bakhtiar Bakhtiar; Fitra Nelli; Firdaus Firdaus (IAIN Manado, 2022)
This article elaborates how ijtihad to changes in the dawn as an effort to integrate sharia and science. With a bibliographic qualitative research method, the author wants to describe how the early dawn changes have been used as guidelines for Muslims. Fajr's schedule has been considered too fast so that it is not in line with the provisions of the texts and the findings of modern science. Muhammadiyah, in its ijtihad, responded openly by making changes to the previous decision compared to the Ministry of Religion and Nadhatul Ulama, which remained in the previous formulation. The study results concluded that reviewing the dawn error at Muhammadiyah had begun in 2016 until it reached maturity in 2020. The results were confirmed at the 31st Tarjih National Conference in 2021 and by the Muhammadiyah Central Executive on March 20, 2021. Effective starting from January 2021, together with the publication of the Muhammadiyah calendar. The Sun's height is the initial criterion for the dawn of time from the original -200. After review, it becomes -180. This change in criteria implies a delay of the early dawn of about eight minutes from the previous one. This change was made to combine aspects of sharia and science with an integrated approach of Bayani, Irfani, and Burhani, considering the benefit of the community.